The Inception Workshop: Co-designing the Project on Potato Production Through Zero Tillage Straw Mulching in Odisha, India - International Potato Center; International Rice Research Institute (2025)
This workshop report documents the inception meeting of the collaborative project Potato Production through Zero Tillage with Rice Straw Mulch (PZTM) held in Bhubaneswar, Odisha, on 14 October 2025. The event brought together 50 participants (25 women, 25 men) from the Government of Odisha, academia, farmer producer organizations (FPOs), women’s self-help groups (SHGs), and private sector partners. PZTM is a women-friendly, climate-smart, and resource-efficient practice that cultivates potatoes directly in rice straw mulch without prior tillage, enhancing soil health, conserving moisture, and reducing greenhouse gas emissions. The workshop focused on co-designing a participatory implementation plan that promotes gender equity and mechanized solutions for scaling. The report highlights discussions on four thematic areas: (1) Women-led scaling models, (2) Mechanized PZTM, (3) Integration with direct-seeded rice (DSR) systems, and (4) Gender-responsive digital advisory services. Field demonstrations and farmer field days are scheduled across Pipili, Nimapada, and Balipatana during the 2025–26 rabi season. The initiative supports CGIAR’s mission to strengthen climate-resilient, inclusive, and sustainable root crop production systems.